Switch from fingolimod to ozanimod for safety or intolerance reasons - Elisabetta Signoriello; Giuseppe Romano; Matteo Foschi; Aurora Zanghì; Emanuele D’Amico; Roberta Fantozzi; Diego Centonze; Giacomo Lus (Therapeutic Advances in Neurological Disorders, 2025)
Introduction: Ozanimod is a new-generation sphingosine-1-phosphate (S1P) modulator, approved for the treatment of multiple sclerosis (MS), offering higher selectivity for S1P receptor 1 and 5 (SPR1-5), minimizing potential safety concerns related to S1P3 receptor activation, compared to fingolimod. Objectives: We aimed to compare the adherence and persistence on treatment in MS patients switched to ozanimod from fingolimod for safety reasons (mainly lymphopenia or liver enzymes increase). Methods: We retrospectively recruited patients treated with fingolimod who switched to ozanimod for safety reasons, with at least 12 months of follow-up. We collected demographic, clinical, biochemistry, and safety data during fingolimod and after switching to ozanimod to evaluate (1) lymphocytes and liver enzymes dynamics, (2) persistence on ozanimod over 6 months, (3) proportion of patients with no adverse events (NADE) on ozanimod and no evidence of disease activity (NEDA-3). Results: We recruited 60 relapsing–remitting MS patients (mean age of 42 ± 7.9 years) who were treated with fingolimod for an average of 5.7 years (61.6% female) and switched to ozanimod due to lymphopenia (70%) or hypertransaminasemia (21.6%). A total of 58/60 (96%) patients persisted on treatment with ozanimod for a mean of 1.50 ± 0.49 years; mean lymphocyte count increased from 0.39 to 0.56 ( p  = 0.025) in patients who switched due to lymphopenia; hypertransaminasemia decreased from 21.6% in fingolimod to 9.3% in ozanimod. NADE was recorded in 93% patients during ozanimod treatment and NEDA-3 in 88.3% of patients after 1 year. Overall, patients with complete control of disease (NEDA) in the absence of adverse events (NADE) were 83.7% (NEDA3/NADE). Discussion and conclusion: Our findings suggest that switching from fingolimod to ozanimod may mitigate lymphopenia or hypertransaminasemia and ameliorate effectiveness on disease activity.